2018
DOI: 10.3389/fpls.2018.01396
|View full text |Cite
|
Sign up to set email alerts
|

Defense Compounds Rather Than Nutrient Availability Shape Aggressiveness Trait Variation Along a Leaf Maturity Gradient in a Biotrophic Plant Pathogen

Abstract: Foliar pathogens face heterogeneous environments depending on the maturity of leaves they interact with. In particular, nutrient availability as well as defense levels may vary significantly, with opposing effects on the success of infection. The present study tested which of these factors have a dominant effect on the pathogen’s development. Poplar leaf disks of eight maturity levels were inoculated with the poplar rust fungus Melampsora larici-populina using an innovative single-spore inoculation procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…On Eucalyptus grandis , all of the steps of the development of the rust Puccinia psidii —germination, appressorium formation, penetration and sporulation—were altered with increased leaf age (Xavier et al, 2015). For other pathosystems, the susceptibility can increase with leaf age, as is the case for another rust, Melampsora larici populina , which is more aggressive on mature leaves of poplar (Maupetit et al, 2018). The authors observed an increase in uredia (colony) size and a higher sporulation rate with increased LPI and lower sporulation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…On Eucalyptus grandis , all of the steps of the development of the rust Puccinia psidii —germination, appressorium formation, penetration and sporulation—were altered with increased leaf age (Xavier et al, 2015). For other pathosystems, the susceptibility can increase with leaf age, as is the case for another rust, Melampsora larici populina , which is more aggressive on mature leaves of poplar (Maupetit et al, 2018). The authors observed an increase in uredia (colony) size and a higher sporulation rate with increased LPI and lower sporulation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they accumulate in host cells to induce protective effects (Daniel and Purkayastha, 1994). Particularly with respect to the defense response to fungal pathogens, phenolic compounds, which are mostly present in leaves, can play functional roles as antioxidants and antimicrobial activities that contribute to plant disease resistance (Shalaby and Horwitz, 2015;Adandonon et al, 2017;Ullah et al, 2017;Maupetit et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We used a single‐spore inoculation protocol: A unique spore is picked with an eyelash and deposited in the center of an excised poplar leaf disk as described in Maupetit et al. (2018). This protocol has several advantages compared with traditional inoculation of foliar pathogens, which usually consists of spraying or depositing a suspension of spores.…”
Section: Methodsmentioning
confidence: 99%
“…This allows the estimation of heritability. This protocol is tedious but has been revealed to be assess reaction norms and trait variations along a gradient of leaf maturity (Maupetit et al., 2018).…”
Section: Methodsmentioning
confidence: 99%